Fetal sensitivity to testosterone, left-handedness and development of bronchial asthma: a new approach - Krommydas, Georgios C.; Molyvdas, Paschalis Adam; Paralikas, Th.; Kotrotsiou, Evangelia; Andreou, Georgia; Gourgoulianis, Konstantinos I.; Raftopoulos, Vasilios (My University, 2004)
In contrast to Geschwind, Behan and Galaburda (GBG) theory, there is strong evidence that inheritance through maternal line is responsible for the coexistence of asthma and left-handedness early in childhood. A new model that incorporates GBG’s theory and maternal inheritance is proposed. This hypothesis suggests that maternal atopy is the most important factor in the evolution of asthma and that GBG’s theory applies mainly in childhood. An inherited enhanced sensitivity of fetus to testosterone may be the underlying mechanism that leads to the development of bronchial asthma.
Keywords: Bronchial asthma; Testosteron